A thematic review of scientific and family interests in Canavan Disease: where are the developmentalists?. (8th June 2012) - Glicksman, S.; Borgen, C.; Blackstein, M.; Gordon, A.; Hanon, I.; Kusin, D.; Leibowitz, B.; Halle, J.
Abstract Background Canavan Disease is a degenerative neurological condition resulting in a spongy deterioration of the brain. Much research has been conducted by the medical community regarding this condition, but little research can be found in the psychological literature. Method A review of the scientific literature related to Canavan Disease using the Psychinfo and PubMed databases was conducted covering a 5‐year span from 2006 through 2011. Concurrently, a review of parent initiated topics found on the most popular Canavan Disease Internet discussion board was conducted for comparison purposes. Results When comparing the topics discussed and information sought among parents with the themes noted in the extant scientific literature, researchers found an exceedingly small overlap between the two communities of interest. In the scientific literature, published research on Canavan Disease focused on three areas: the biochemistry of Canavan Disease, diagnosis and genetic counselling, and clinical therapeutic approaches in Canavan Disease. Of the 42 unique topics raised on a popular Internet discussion board, however, only three (7%) fell into the category of diagnosis and genetic counselling, none (0%) fell into the category of the biochemistry of Canavan Disease, and four fell into the category of clinical therapeutic approaches in Canavan Disease (10%). Of the four posts addressing clinical therapeutic approaches to Canavan Disease, only one post truly overlapped with the topics addressed by the scientific community. Worded differently, while these three categories comprise 100% of the extant scientific literature regarding Canavan Disease, they comprise only 17% of the parent‐raised topics. The remaining 83% of parent‐raised topics addressed concerns not currently being focusing upon by the scientific community, namely, non‐medical practical issues, information regarding specific characteristics of Canavan Disease, non‐medical developmental and quality of life issues, and day‐to‐day developmental and medical concerns. Conclusion By comparing the extant literature on Canavan Disease with the topics of interest raised by parents and caregivers, it seems clear that there is a significant 'underlap' of topics raised by these two communities of interest, one that may reflect a lack of sensitivity on the part of the scientific community to meet the needs of this population of knowledge seekers. It is the suggestion of these authors that developmental psychology may be the appropriate scientific field within which to address this need and fill this gap in the current literature.